EFFECT OF DRYING METHODS ON DRYING CHARACTERISTIC, ENERGY CONSUMPTION AND COLOR OF NECTARINE - Ismail, Osman; Beyribey, Berceste; Doymaz, Ibrahim (YILDIZ TECHNICAL UNIV, 2016)
The effect of drying methods on drying characteristic, energy consumption and color has been investigated for nectarine in this study. Sun, hot air, microwave and infrared drying techniques were applied as drying methods. The drying temperature was determined as 50 degrees C for hot air drying of nectarine, as the applied powers were 90W and 83W for microwave and infrared dryings, respectively. The results obtained from the experiments indicate that the microwave drying method is the most effective method for drying of nectarine. The higher L'' value and lower -a/b'' ratio values were obtained in hot-air dried nectarine slices. The results have been modelled with six different models in the literature to determine the drying kinetics for nectarine. Comparing the high R-2, low RMSE and chi(2) values for all drying methods; it is presented that Midilli et al. model is the most convenient model for drying of nectarine.
Keywords: Drying models; drying time; color; energy consumption; LAYER; MICROWAVE; KINETICS; Thermodynamics